2017
DOI: 10.1158/1055-9965.epi-16-0927
|View full text |Cite
|
Sign up to set email alerts
|

Kernel Density Estimation as a Measure of Environmental Exposure Related to Insulin Resistance in Breast Cancer Survivors

Abstract: Background Environmental factors may influence breast cancer, however most studies have measured environmental exposure in neighborhoods around home residences (static exposure). We hypothesize that tracking environmental exposures over time and space (dynamic exposure) is key to assessing total exposure. This study compares breast cancer survivors' exposure to walkable and recreation-promoting environments using dynamic Global Positioning System (GPS) and static home-based measures of exposure in relation to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 62 publications
(51 reference statements)
0
7
0
Order By: Relevance
“…Participantsā€™ GPS data points over their 14-day device wear period were used to generate a time-weighted activity space surface using a 200-m-bandwidth KDE function. The time-weighted activity space was then multiplied by the walkability index, comprising intersection density, residential density, and land use mix, to produce the average dynamic walkability exposure variable [ 68 ].…”
Section: Methodsmentioning
confidence: 99%
“…Participantsā€™ GPS data points over their 14-day device wear period were used to generate a time-weighted activity space surface using a 200-m-bandwidth KDE function. The time-weighted activity space was then multiplied by the walkability index, comprising intersection density, residential density, and land use mix, to produce the average dynamic walkability exposure variable [ 68 ].…”
Section: Methodsmentioning
confidence: 99%
“…Walkability scale [ 81 ]; Buffer-level walkability [ 68 ]; per grid unit [ 82 ]; walkability score [ 74 ]…”
Section: Figurementioning
confidence: 99%
“…Geospatial distribution of sheep and goats exposed to T. gondii Small ruminants are intermediate hosts of T. gondii, which are highly susceptible to T. gondii and, chronically infectious for life. It is believed that the parasite is a major cause of abortion and neonatal mortality in sheep and goats, resulting in economic loss [13][14]. Furthermore, consumption of raw or undercooked meat from these animals has been regarded as a major route of T. gondii transmission to humans, especially in countries and regions where mutton and beef is regularly eaten [15].…”
Section: Geospatial Distribution Of Livestock Exposed To T Gondii In Chinamentioning
confidence: 99%
“…It has been reported that isolating T. gondii from seropositive cattle were often unsuccessful, however Dubey JP [18] showed that viable tissue cysts can remain in cattle for up to 1 191 days. Hence, the contaminated cattle and yaks may be an important source for T. gondii transmitted to other animals and humans in China [14]. The geospatial distribution of toxoplasmosis in cattle and yaks in China is shown in Fig.…”
Section: Geospatial Distribution Of Livestock Exposed To T Gondii In Chinamentioning
confidence: 99%